Eero Tarasti, existential semiotics, music, and mind. On the existential and cognitive notions of situation - Ojala, Juha (Mouton De Gruyter, 2023)
In recent decades, there has been a shift both in semiotics and in cognitive science to novel, perhaps more flexible currents of research. This applies to semiotic and cognitive musicology as well, and raises interest in the conceptual correlates in the historical shifts, particularly in how the shifts have opened avenue for addressing both the social and cultural, and the subject’s embodied mind in the study of signification within a systematic framework. Emblematic of the paradigmatic shifts, situation emerges as a key notion. From the current, pragmatist perspective, a comparison of Eero Tarasti’s existential-semiotic and Mauri Kaipainen’s cognitive notions of situation reveals striking similarities. For one, situations become meaningful only in their contexts and through their use, as they are dynamically established in the processes of being in the world. Besides the evident methodological and topical differences, fundamental differences are to be found in the attention paid to the epistemic conditions of subject’s being in the world, and the acknowledged complexity of the situations, illustrated by the recursive agent/patient-levels by Tarasti. For the study of musical signification, the pragmatist approach may help reconcile the differencies, contributing to the necessary groundwork for a theory that could incorporate complex, iterative levels of narration spanning between signs as acts, stylistic constraints of musical discourse, social contexts, and epistemes of culture, while also taking into account the view of mind as embodied, embedded, enactive, and extended cognition.
Keywords: Tarasti, Eero